Internet of Things : integration and security challenges - Velliangiri, S.; Kumar, Sathish A. P.; Karthikeyan, P., 1981- (Boca Raton : CRC Press, 2020)
IoT is empowered by various technologies used to detect, gather, store, act, process, transmit, oversee, and examine information. The combination of emergent technologies for information processing and distributed security, such as Cloud computing, Artificial intelligence, and Blockchain, brings new challenges in addressing distributed security methods that form the foundation of improved and eventually entirely new products and services. As systems interact with each other, it is essential to have an agreed interoperability standard, which is safe and valid. This book aims at providing an introduction by illustrating state-of-the-art security challenges and threats in IoT and the latest developments in IoT with Cloud, AI, and Blockchain security challenges. Various application case studies from domains such as science, engineering, and healthcare are introduced, along with their architecture and how they leverage various technologies Cloud, AI, and Blockchain. This book provides a comprehensive guide to researchers and students to design IoT integrated AI, Cloud, and Blockchain projects and to have an overview of the next generation challenges that may arise in the coming years.
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things -- Security measures; COMPUTERS / Database Management / Data Mining; COMPUTERS / Internet / Security; TECHNOLOGY / Manufacturing